Specification for rated capacities of fork lift trucks - British Standards Institution (London BSI, 1968)
Fork trucks, High-lift trucks, Industrial trucks, Lifting, Height, Performance, Marking, Ratings, Load capacity, Powered industrial trucks
Withdrawn
Cross References BS 350, BS 3726, PD 5686
Keywords: Fork lift trucks -- Standards